Conversion of array‐based single nucleotide polymorphic markers for use in targeted genotyping by sequencing in hexaploid wheat (Triticum aestivum). Issue 4 (23rd October 2017) - Burridge, Amanda J.; Wilkinson, Paul A.; Winfield, Mark O.; Barker, Gary L. A.; Allen, Alexandra M.; Coghill, Jane A.; Waterfall, Christy; Edwards, Keith J.
Summary: Wheat breeders and academics alike use single nucleotide polymorphisms (SNPs) as molecular markers to characterize regions of interest within the hexaploid wheat genome. A number of SNP‐based genotyping platforms are available, and their utility depends upon factors such as the available technologies, number of data points required, budgets and the technical expertise required. Unfortunately, markers can rarely be exchanged between existing and newly developed platforms, meaning that previously generated data cannot be compared, or combined, with more recently generated data sets. We predict that genotyping by sequencing will become the predominant genotyping technology within the next 5–10 years. With this in mind, to ensure that data generated from current genotyping platforms continues to be of use, we have designed and utilized SNP‐based capture probes from several thousand existing and publicly available probes from Axiom® and KASP™ genotyping platforms. We have validated our capture probes in a targeted genotyping by sequencing protocol using 31 previously genotyped UK elite hexaploid wheat accessions. Data comparisons between targeted genotyping by sequencing, Axiom® array genotyping and KASP™ genotyping assays, identified a set of 3256 probes which reliably bring together targeted genotyping by sequencing data with the previously available marker data set. As such, these probes are likely to be of considerable value to the wheat community. The probe details, full probe sequences and a custom built analysis pipeline may be freely downloaded from the CerealsDB website (http://www.cerealsdb.uk.net/cerealgenomics/CerealsDB/sequence_capture.php).